Analisis Inovasi Pelayanan Publik "Kelas Perahu" Kabupaten Pangkajene dan Kepulauan - Dian Sari (SAP (Susunan Artikel Pendidikan), 2019)
Kelas Perahu is one of the public service innovations in the education sector that received the Top 40 Public Service Innovation 2018 Award. Kelas Perahu are intended to reduce the number of drop-out rates on the islands in the Pangkajene and Islands Districts. For one year the School Participation Rate (APS) was implemented in Pangkajene and Kepulauan Districts at the Primary School level, reaching 100 percent and the junior high school level rose by 1.16 percent. Indonesia is an archipelagic country that allows Kelas Perahu to be able to improve their quality and can be used in other islands, therefore in this study aims to analyze Kelas Perahu service innovations in terms of understanding, success of Kelas Perahu and analyzing from a post managerial perspective. Analysis is carried out using the desk study method, which collects secondary data to draw conclusions with descriptive qualitative methods. From the results of the research conducted, the Kelas Perahu is a service innovation in education that is new, useful, and in accordance with public expectations, then can be continued by making the boat class not only fulfilling the government's compulsory education program, but also influencing other sectors